Faith for the times ; pt 2 studies in the prophecy of Isaiah chapters 49 to 54 - Redpath, Alan (London, UK Pickering and Inglis, 1974)
Contents : pt 2 : The plan of deliverance.
Keywords: Bible. O.T. Isaiah XLIX-LIV -- criticism, interpretation, etc